REVISITING DONALD MOON ON THE MORAL BASIS OF THE DEMOCRATIC WELFARE STATE - ADEYANJU, Olanshile Muideen (Studia Universitatis Babeș-Bolyai Philosophia, 2023)
Donald Moon argues that neither rights nor equality can serve as adequate moral or political basis for a welfare state in addressing the Hegel’s dilemma. The Hegel’s dilemma is that organisation of economic life through the market in a democratic state produces great wealth as well as great poverty and individuals in such state fall in either category. The wide gulf in wealth among individuals in a market economy is a problem which a democratic welfare state seeks to address but, for Moon, rights or equality is not adequate moral and political basis of the welfare state for solving the problem. He proposes the principles of economic management, provision of services and social insurance as alternative and adequate bases for a welfare state in addressing the problem. This paper queries Moon’s proposal. The paper argues that Moon’s proposed institutional principles are inadequate in addressing the problem without a fundamental moral and/or political basis upon which these principles can be justifiably founded. The paper posits that rights provide a plausible and adequate foundational moral and political basis for the principles in order to adequately address the problem created by the market economy without jeopardising the idea of human self-respect.